O discurso de formação de professores: tensões e valores na produção de sentido - Ferreira, Anderson (2014)
This research is based on studies of the francophone Discourse Analysis and theme is the study of the organization and functioning of discourse in the School of Development and Improvement of Teachers of São Paulo - SDIT, produced under the Department of Education State of Sao Paulo - DESSP. Justified in the present study the possibility of examining how the values and tensions in the discourse of teacher education offered by DESSP are generated, since the circumscribed speeches in Training School mitigate issues essential to the promotion of quality education in nowadays, such as violence in schools, the precariousness of public education, professional development, the autonomy of school management and continuing education of teachers. Our research aims to examine how discursive practices, discourses that produce teacher education at the institutional level, seeking to contribute to the study of discourse and interdiscursive reading in teacher training. The categories of analysis that operationalize reveal us that the discourse of teacher education is rooted in economic and political factors , the hegemonic pedagogies and respond more readily to these clashes , apparently the school setting . The analysis of the relationship of speech interdiscursive SDIT made us watch values and tensions it engenders , but it was from the constitution of the scenography and the discursive ethos that we could see the working mechanisms of this discourse